Penentuan Kadar Fenolik Total Dan Peredaman Radikal Bebas Ekstrak Metanol Daun Bayam Hijau (Amaranthus hybridus L) Dengan DPPH - Nurhasanah, Devika; Mafa , Sutri Hud; Pratama, Nofran (JOURNAL OF PHARMACEUTICAL (JOP), 2024)
Background: Free radicals are molecules that have one or more free or unpaired electrons, so that free radicals are unstable. Free radicals can be inhibited in the presence of antioxidant compounds. The compound antioxidant can be obtained from various sources, one of which is from the green spinach plant. Amaranthus hybridus L. is a herbaceous plant from the Amaranthaceae family that contains natural antioxidant compounds, namely phenolic compounds. Objective: This study aimed to determine the total phenolic levels contained in methanol extract of Amaranthus hybridus L. and what is the value of IC50 methanol extract of Amaranthus hybridus L. which is able to reduce DPPH free radicals. Method: Amaranthus hybridus L. were extracted with methanol solvent by maceration method in a ratio (1:10). Then a qualitative analysis was carried out in the form of phytochemical screening, identification of phenolic compounds by Thin Layer Chromatography (TLC) method using the methanol mobile phase: chloroform: n-hexane (1:9:1 v/v/v) and the stationary phase of silica gel GF254. Quantitative analysis of the total phenolic content test, and free radical suppression activity test by DPPH method which was measured using a UV-Vis spectrophotometer to calculate IC50. Result: Methanol extract of Amaranthus hybridus L. positively contains alkaloid compounds, phenolics, flavonoids, saponins, and tannins. The TLC Rf quercetin value is 0.475, and the Rf extract is two spots namely 0.35 and 0.837. Total phenolic content of 1.150 ± 0.025% and a free radical suppression activity of IC50 value of 14.786 ppm. Conclusion: Methanol extract of Amaranthus hybridus L. could be categorized as very strong.